Pijat Tuina Sebagai Terapi Alami Untuk Mengatasi Picky Eater Pada Balita - Sumarni, Sumarni; Rinda Izdihar Khoirunnisa; Silmi Ardiatun Madani; Tanti Tri Persadawati; Tri Wahyu Retno Ambarwati; Vaniria Rindi Antika; Alya Putri Andini (jurnal ABDIMAS Indonesia, 2025)
Tui na massage is one of the non-pharmacological therapies that can be done to overcome picky eaters in toddlers. Tui na massage therapy aims to improve digestion and blood circulation in the spleen. This counseling method is carried out directly with interactive lectures and discussions as well as tui na massage simulations. Discussions are carried out using the Q&A method related to the material. Tui na massage is carried out using techniques such as massaging (Petrissage or Nie), tapping (Tapotement or Da), gliding (Effleurage or Tui), friction, rotating, and vibrating certain points so that they will affect the body's energy. This therapy is carried out once a day for 6 consecutive days. The results of the activity showed that after this activity most mothers had good knowledge about picky eaters and tui na massage. This counseling activity has been achieved by increasing insight in mothers of toddlers.